An outbreak of animal trypanosomosis in a fulani herd at Idofian in Kwara State Nigeria (2005)
An epizootiological investigation was conducted to establish the cause of an outbreak of a disease which reportedly resulted in fifty cases of abortions and thirty deaths out of a population of 1,200-cattle within one month after its onset. The incident occurred in a Fulani.farm settlement located on the outskirt of Idofian via-Ilorin, Kwara State, Nigeria. Using parasitological methods, 9 out of the 34 animals sampled from the herd; were positive for trypanosoniosis, indicating 26.47% prevalence of the disease in the farm; Trypanosoma vivax was detected in seven of the samples while T. congolense was present in two. This finding coupled with other epizootiological parameters examined established trypanosoniosis outbreak in the herd which might have resulted in the reported cases of abortion and death among the cattle. The finding underscores how the disease can still be a major impediment to the growth of cattle enterprise in some parts of Nigeria.